2022
DOI: 10.1055/a-1852-0330
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence-assisted optical diagnosis for the resect-and-discard strategy in clinical practice: the Artificial intelligence BLI Characterization (ABC) study

Abstract: Background and aim: Optical diagnosis (OD) of colonic polyps is poorly reproducible outside high-volume referral centres. Present study aimed to assess whether real-time AI-assisted OD is accurate enough to implement the leave-in-situ strategy for diminutive (5mm) rectosigmoid (DRSPs) polyps. Methods: Consecutive colonoscopy outpatients with 5mm) rectosigmoid (DRSPs) polyps. Methods: Consecutive colonoscopy outpatients with >1 DRSP were included. DRSPs were categorized as adenomas or non-adenomas by the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
71
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 32 publications
3
71
2
1
Order By: Relevance
“…The other Italian clinical study [ 36 ] evaluated the performance of the CAD-EYE CADx module (Fujifilm, Japan), which delivers an optical diagnosis dynamically during live colonoscopy every time virtual chromoendoscopy is activated during the procedure. This system also provides a heat map of the area most likely to harbor the provided diagnosis.…”
Section: Cadxmentioning
confidence: 99%
“…The other Italian clinical study [ 36 ] evaluated the performance of the CAD-EYE CADx module (Fujifilm, Japan), which delivers an optical diagnosis dynamically during live colonoscopy every time virtual chromoendoscopy is activated during the procedure. This system also provides a heat map of the area most likely to harbor the provided diagnosis.…”
Section: Cadxmentioning
confidence: 99%
“…Two trials 114 115 from the same Japanese group, using a CADx system and employing endocytomicroscopy and NBI, showed conflicting results, the first concluding that the system could meet required thresholds, while the second, in a multicenter setting with less experienced endoscopists, failed to reach acceptable levels. Another single-center study 116 involving 162 patients with 544 polyps showed that an approved CADx system exceeded PIVI thresholds for implementation in clinical practice, while a multicenter experience 117 with another approved CADx system fell short of required thresholds.…”
Section: Lower Gi Tractmentioning
confidence: 99%
“…These advances have already led to the introduction of the first commercially available, regulatory-approved CADx systems [6]. Although several of these CADx systems were able to reach the PIVI and SODA thresholds within prospective validation settings, none of the systems have yet been able to reach all performance thresholds [7][8][9][10][11]. In addition, there remain several limitations that might hamper widespread implementation of these systems in clinical practice [12].…”
Section: Introductionmentioning
confidence: 99%